Photovoltaic system faults diagnosis using discrete wavelet transform based artificial neural networks - Bengharbi, Abdelkader Azzeddine; Laribi, Saadi Souad; Allaoui, Tayeb; Mimouni, Amina (Національний технічний університет "Харківський політехнічний інститут", 2022)
Introduction. This research work focuses on the design and experimental validation of fault detection techniques in grid-connected solar photovoltaic system operating under Maximum Power Point Tracking mode and subjected to various operating conditions. Purpose. Six fault scenarios are considered in this study including partial shading, open circuit in the photovoltaic array, complete failure of one of the six IGBTs of the inverter and some parametric faults that may appear in controller of the boost converter. Methods. The fault detection technique developed in this work is based on artificial neural networks and uses discrete wavelet transform to extract the features for the identification of the underlying faults. By applying discrete wavelet transform, the time domain inverter output current is decomposed into different frequency bands, and then the root mean square values at each frequency band are used to train the neural network. Results. The proposed fault diagnosis method has been extensively tested on the above faults scenarios and proved to be very effective and extremely accurate under large variations in the irradiance and temperature.

Вступ. Ця дослідницька робота присвячена розробці та експериментальній перевірці методів виявлення несправностей у підключеній до мережі сонячній фотоелектричній системі, що працює в режимі відстеження точки максимальної потужності та піддається різним умовам експлуатації. Мета. У цьому дослідженні розглядаються шість сценаріїв відмови, включаючи часткове затінення, обрив кола у фотогальванічній батареї, повна відмова одного з шести IGBT інвертора та деякі параметричні відмови, які можуть виникнути в контролері перетворювача, що підвищує. Методи. Методика виявлення несправностей, розроблена у цій роботі, полягає в штучних нейронних мережах і використовує дискретне вейвлет-перетворення для отримання ознак для ідентифікації основних несправностей. Застосовуючи дискретне вейвлет-перетворення, вихідний струм інвертора в часовій області розкладається на різні смуги частот, а потім середньоквадратичні значення в кожній смузі частот використовуються для навчання нейронної мережі. Результати. Запропонований метод діагностики несправностей був всебічно протестований на вказаних вище сценаріях несправностей і виявився дуже ефективним і надзвичайно точним при великих коливаннях освітленості і температури.
Keywords: artificial neural network; discrete wavelet transform; fault diagnosis; photovoltaic system; штучна нейронна мережа; дискретне вейвлет-перетворення; діагностика несправностей; фотоелектрична система